MANAJEMEN DAN EFISIENSI PENDIDIKAN: KECENDERUNGAN DAN DAMPAK KEBIJAKAN - Aprilliantoni, Aprilliantoni; Nujud, Yasub Atsyir; Rafa, Juana; Pasaribu, Muhammad Syafaruddin (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research aims to provide a description of several problems that occur in education in Indonesia which become an illustration of the role of education management, and also to analyze trends in education management and the impact of policies on the efficiency of the education system. Specifically, this research aims to determine (a.) The role of educational management in education in Indonesia. (b.) The influence of School-Based Management (SBM) which is used as an efficient effort in solving educational problems in Indonesia. The research method used by the author in this research uses a descriptive qualitative research method with data collection techniques using literature studies sourced from interviews, books, journals, documents and also valid websites. The results of this research show that efficient education management is a key factor in improving the quality and accessibility of education, especially in developing countries like Indonesia.